How social media and peer learning influence student-teacher self-directed learning in an online world under the New Normal - Paitoon Pimdee; Attaporn Ridhikerd; Sangutai Moto; Surapong Siripongdee; Suwanna Bengthong (My University, 2023)
The study aimed to investigate three aspects of Thai student-teacher self-directed learning (SDL) competency. These were the student-teachers opinions concerning their use of social media (SM), self-management (SM), and learning desire (LD). The sample group was 468 student-teachers enrolled in a Bachelor of Industrial Education Program at the King Mongkut's Institute of Technology Ladkrabang in Bangkok, Thailand, in the Academic Year 2021. The research instrument consisted of an SDL competency questionnaire whose discrimination (corrected item-total correlation) values were determined to be between 0.37 and 0.69, which also had a confidence level of 0.91. Data analysis used LISREL 9.10 for the study's second-order confirmatory factor analysis (CFA). Descriptive statistics analysis included the mean and standard deviation (SD), which was accomplished using IBM's® SPSS® for Windows Version 21. Three models were developed for the study. These included the social media (SM) model containing 285 participants, the peer learning (PL) model, which contained 183 participants, and the total group (TG) model, which contained everyone surveyed (n = 468). The final analysis from the second-order CFAs showed that student-teacher SDL competency for self-control (SC) (0.96) was valued most by the student-teachers. However, their learning desire (LD) (0.87) and self-management (SM) (0.80) skills were somewhat behind. Moreover, in the Pearson Product Moment Correlation (PPMC) (r) analysis of the 24 variable relationships, the strongest was related to each student-teacher's learning desire. However, the weakest variable relationship was related to their ability to set high personal standards and the self-discipline to achieve them. Finally, quite interestingly, 60.90% of the student-teachers indicated that their SDL is gotten from social media (SM) resources compared to learning from their peers (PL) around them.
Keywords: Bachelor; LISREL; Technology-Enhanced Education Studies